Learning From the Advanced Education System in Finland - Rahmi, Tysa Sufia; Mardiyah, Ainul; Yusra, Alfajri; Rusdinal, Rusdinal; Gistituati, Nurhizrah; Ananda, Azwar (Postgraduate School, Universitas Negeri Padang, 2023)
The background of writing this article is to see the problem of education in Indonesia that has not been able to fully produce quality human beings, this is due to the quality of education in Indonesia that has not been maximized. For this reason, it is necessary to improve the quality of education in Indonesia by improving the responsive education system to answer the changes and demands of the times, therefore we need to learn from one of the countries that has the best education system in the world, namely Finland. The advancement of the education system in Finland can certainly be used as an example of the implementation of education in Indonesia. The purpose of writing this article is to see the advanced education system in Finland. The method used in compiling this article is a literature study, A literature study is a variety of sources, ranging from books, articles, and various references related to the advancement of the education system in Finland. The results showed that the advanced education system in Finland can be seen from several aspects of the implementation of education in the country, including teachers, learning environment, evaluation, and school curriculum.